Application of Compost Leaves of Sengon Fertilizer (Paraserianthes Falcataria L.) as Substitution of Inorganic Fertilizer on The Growth and Production of Two Varieties of Soybean (Glycine Max L.) - Juwono, Fahmi; Widjajanto, Didik Wisnu; Sutarno (Jurnal Online Pertanian Tropik, 2020)
ABSTRACT This study was aimed to examine the effect of the substitution of compost leaves of sengon (Paraserianthes falcataria L.) on inorganic fertilizer on the growth and production of two varieties of soybean (Glycine max L.). The study was conducted on January to April 2019 at greenhouse, Laboratory of Ecology and Plant Production, Faculty of Animal and Agricultural Science, Diponegoro University. A completely randomized design (CRD) with 5 replications was used throughout the study. The first factor consisted of no compost and an inorganic fertilizer substitution, 25%, 50%, 75%, 100% compost substitution, respectively, and 100% of inorganic fertilizers. The second factor was two soybean varieties, namely detam 3 prida and malica. The parameters observed were number of branches, number of trifoliate leaves, number of pods, number of seeds, seed weight, the 100-seed weight. Data were analyzed using ANOVA and continued with the Duncan’s Multiple Range Test at a significant level of 5%. The results showed that the dose of compost substitution affected the parameters of the number of branches, number of pods and number of seeds significantly. Soybean detam 3 prida varieties showed a significant effect on the number of branches and the 100-seed weight, while malika varieties showed a significant effect on the number of pods. Substitution dose of 75% compost (26.19 N/ha) showed the highest results on the parameters of the number of branches, number of pods, number of seeds, weight of seeds and the 100-seed weight, and resulted as the highest yield compared to no substitution on all plant parameters. On the basis of the data found throughout the experiment may be concluded that 75% compost of leaves sengon was the most suitable doses to be applied at the cultivation of soybean especially varieties of detam 3 prida and malica. Keywords: compost, detam, malika, soybean REFERENCES Adisarwanto, T. 2005. Kedelai. Penebar Swadaya, Jakarta. Adisarwanto, T. dan R. Wudianto. 2008. Meningkatkan hasil panen kedelai di lahan sawah-kering-pasang surut kedelai. Penebar Swadaya, Jakarta. Badan Penelitian dan Pengembangan Pertanian, 2008. Mutu Kedelai Nasional Lebih Baik dari Kedelai Impor. SiaranPers, Jakarta. Badan Pusat Statistik (BPS). 2015. Produksi Kedelai menurut Provinsi (ton), 1993-2015. http://www.bps.go.id. Accessed November 11, 2019. Badan Pusat Statistik (BPS). 2019. Statistik Daerah Kota Semarang 2019. http://www.bps.go.id. Accessed February 10, 2020. Balai Penelitian Tanaman Aneka Kacang dan Ubi. 2013. Deskripsi Varietas Unggul Aneka Kacang dan Umbi. Balitkabi, Malang. Gabesius, Y. O., L. A. M. Siregar dan Y. Husni. 2012. Respon Pertumbuhan dan Produksi Beberapa Varietas Kedelai (Glycine max L. Merill.) Terhadap Pemberian Pupuk Bokashi. J. Online Agroekoteknologi 31(1): 220-236. Ginting, E., dan R. Yulifianti. 2014. Kualitas dan preferensi industri terhadap kecap dari varietas unggul kedelai hitam. Balai Penelitian Tanaman Aneka Kacang dan Umbi. Prosiding Seminar Hasil Penelitian Tanaman Aneka Kacang dan Umbi. Malang. 452-465. Harsono dan Suryantini. 2011. Kacang Nagara. Balai Informasi Pertanian. Banjarbaru, Kalimantan Selatan 5:1-2. Istarofah., dan Z. Salamah. 2017. Pertumbuhan tanaman sawi hijau (Brassica juncea L.) dengan pemberian kompos berbahan dasar daun paitan (Thitonia diversifolia L.). Bio-Site. 3 (1) : 39 “ 46. Kumudini, S., P. Pallikonda, C. Steele. 2007. Photoperiod and E-genes direcly influence the duration of soybean reproductive development. Crop Sci. 47: 1510-1577. Marliah, A., T. Hidayat, dan N. Husna. 2012. Pengaruh varietas dan jarak tanam terhadap pertumbuhan kedelai (Glycine max (L). Merrill.) J. Agrista 16(1): 22-28. Mejaya, I. M., A. Krisnawati, H. Kuswantoro. 2010. Identifikasi plasma nutfah kedelai berumur genjah dan berdaya hasil tinggi. Bul. Plasma Nutfah 16: 113-117. Musnawar, E. I. 2005. Pupuk Organik Padat. Penebar Swadaya, Jakarta. Muzammil, D., Rusmawan., Asmarhansyah. 2010. Pengaruh Dosis Nitrogen Terhadap Pertumbuhan Dan Produksi Kedelai Di Lahan Bekas Tambang Timah Bangka Tengah, Kepulauan Bangka Belitung. Balai Pengkajian Teknologi Pertanian Kepulauan Bangka Belitung. Novizan. 2007. Petunjuk Pempukan yang Efektif. AgroMedia Pustaka, Jakarta. Pandiangan, D.N., dan A. Rasyad. 2017. Komponen hasil dan mutu biji beberapa varietas tanaman kedelai (Glycine max (L). Merrill.) yang ditanam pada empat waktu aplikasi pupuk nitrogen. JOM Faperta 4(2): 1-14. Sarawa., A. A. Anas, dan Asrida. 2014. Pola distribusi fotosintat pada fase vegetatif beberapa varietas kedelai pada tanah masam di Sulawesi tenggara. J. Agroteknos 4(1): 50-54. Widiyanto, A. dan A. Sudomo. 2014. Pengaruh pemberian pangkasan sengon terhadap pertumbuhan sengon dan produksi kacang tanah dalam sistem agroforestry. J. Penelitian Agroforestry, 2(1): 1“12.